Pengaruh Indikator Kelembagaan terhadap Indikator Dampak Zakat pada Lembaga Amil Zakat di Indonesia - Agnes Yulyanti; Ifa Hanifia Senjiati; Iwan Permana (Bandung Conference Series: Sharia Economic Law, 2022)
Abstract. The potential for collecting zakat funds in Indonesia is quite large and is expected to help reduce poverty and improve people's welfare. In this case, LAZ as a zakat management organization that is managed independently by the community has a very important role because the absorption of zakat funds by LAZ is greater than BAZNAS. However, according to BPS data, the poverty rate in Indonesia is still increasing. Therefore, this study focused on evaluating the performance of LAZ based on institutional indicators with the aim of knowing the description of institutional indicators on LAZ in Indonesia, description of indicators of the impact of zakat on LAZ in Indonesia and the influence of institutional indicators on indicators of the impact of zakat on LAZ in Indonesia. Based on this phenomenon, the problem of this research is formulated as follows (1) What is the picture of institutional indicators on LAZ in Indonesia? (2) What are the indicators of the impact of zakat on LAZ in Indonesia? (3) How is the influence of institutional indicators on indicators of the impact of zakat on LAZ in Indonesia?. The research method used is descriptive verification with data analysis carried out through statistical calculations. The results of the study show that institutional indicators and impact indicators on LAZ in Indonesia are in a fairly good category and there is an influence of institutional indicators on indicators of the impact of zakat on LAZ in Indonesia. Abstrak. Potensi pengumpulan dana zakat di Indonesia cukup besar dan diharapkan dapat membantu menekan angka kemiskinan serta meningkatkan kesejahteraan masyarakat. Dalam hal ini, LAZ sebagai organisasi pengelola zakat yang dikelola masyarakat secara swadaya memiliki peran yang sangat penting karena penyerapan dana zakat yang dilakukan LAZ lebih besar dari BAZNAS. Namun demikian, menurut data BPS, tingkat kemiskinan di Indonesia masih mengalami peningkatan. Oleh karena itu, maka penelitian ini di fokuskan untuk mengevaluasi kinerja LAZ berdasarkan indikator kelembagaan dengan tujuan untuk mengetahui gambaran indikator kelembagaan pada LAZ di Indonesia, gambaran indikator dampak zakat pada LAZ di Indonesia dan pengaruh indikator kelembagaan terhadap indikator dampak zakat pada LAZ di Indonesia. Berdasarkan fenomena tersebut, maka permasalahan penelilian ini dirumuskan sebagai berikut: (1) Bagaimana gambaran indikator kelembagaan pada LAZ di Indonesia? (2) Bagaimana gambaran indikator dampak zakat pada LAZ di Indonesia? (3) Bagaimana pengaruh Indikator kelembagaan terhadap indikator dampak zakat pada LAZ di Indonesia?. Metode penelitian yang digunakan adalah deskriptif verivikatif dengan analisis data dilakukan melalui penghitungan statistik. Hasil penelitian menunjukkan bahwa indikator kelembagaan dan indikator dampak zakat pada LAZ di Indonesia berada pada kategori cukup baik serta terdapat pengaruh indikator kelembagaan terhadap indikator dampak zakat pada LAZ di Indonesia.